Consequences of Downward Envy: A Model of Self-esteem Threat, Abusive Supervision, and Supervisory Leader Self-improvement - Yu, Lingtao; Duffy, Michelle K.; Tepper, Bennett J. (Academy of Management Journal, 2018)
We invoke theory and research on the social functional view of envy to propose a novel theoretical framework of supervisory leader envy of direct reports. Findings from two multi-source, multi-wave studies of supervisor–subordinate dyads provide support for the theses that (1) downward envy of subordinates threatens supervisors’ self-esteem and triggers adaptive strategies in the form of abusive supervision and supervisory self-improvement; and (2) supervisors are more likely to respond to downward envy induced self-esteem threat with abuse when they perceive envied subordinates to be cold and competent and they are more likely to respond with self-improvement when they perceive envied subordinates to be warm and competent.